Inverse-Dash Rectangular Slot 2x4 Array 5.8 GHz Antenna for Multiple Access Integration of IoT Systems and Terrestrial Satellite Communication Networks - Irfan Mujahiddin; Budi Basuki Subagio; Roni Apriantoro; Muhlasah Novitasari Mara; Siti Hasanah; Akio Kitagawa (International Journal of Integrated Engineering, 2025)
LEO satellites provide a phenomenal solution for the provision of internet networks around the world, especially in remote areas. Along with this, the increasing demand for fast and stable information and communication network access technology, especially in applications such as the Internet of Things (IoT) and satellite communications, demands innovative solutions to overcome infrastructure limitations in remote areas. From 2022 to 2026, this need is expected to increase by around 25%. IoT technology, which is key in the industrial revolution 4.0 and the development of smart cities, relies heavily on the support of communication networks, especially in remote areas that are underserved by mobile and fiber optic infrastructure. This study proposes an optimal antenna design for point-to-point applications on WLAN-IoT networks integrated with LEO satellite communication systems. The antenna design uses a rectangular inverted-dash patch-shaped array configuration with an operating frequency of 5.8 GHz, designed to improve communication range and efficiency. The antenna has a high gain of 5 dBi and a directional radiation pattern that is suitable for difficult environments in remote areas. The prototype antenna test showed positive results with a return loss of -15.78 dB, a VSWR of 1.39, and a radiation efficiency of 96%. The test results also showed a significant increase in transmission signal strength compared to the reference antenna, providing an innovative solution to extend the range of the satellite communication system with high efficiency. This study emphasizes the importance of antenna design that takes into account technical specifications and environmental conditions to optimize the performance of communication networks in remote areas.